Unlearning Colonialism by Attending to the Wisdom of Relational Renewal - Donald, Dwayne; Tait, Lesley; Moostoos-Lafferty, Etienna (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
This article hinges on the conviction that the centuries-long dominance of colonial worldview has resulted in the creation of educational practices that perpetuate colonial forms of relationship denial in mostly subtle and unquestioned ways. As part of an ongoing effort to honour knowledge systems and ways of being that are not fully circumscribed by such colonial logics, we participated in a unique graduate course offered at the University of Alberta. The intention of the course is to engage with the wisdom teachings of relational renewal for the duration of the 13 Moon calendar, which shapes and characterizes the patterns of life and living that have been followed by Indigenous peoples in the northern plains region of North America for millennia. We share reflective insights from course participants, bring focus to three nêhiyaw (Cree) wisdom concepts, and conceptualize a model for unlearning colonial forms of relationship denial that emerges from our engagement with the course experience.